New species and new records of the flora in Amotape-Huancabamba Zone: Endemics and biogeographic limits - Weigend, Maximiliam (2005)
The taxonomy of the Ribes andicola group and Urtica is investigated for the relict forests in the AmotapeHuancabamba Zone and especially the relict forests of NW Peru. Three new species of Ribes are described, Ribes contumazensis as local endemic from Contumazá, R. colandina as widespread across the Andes from Lambayeque and La Libertad to Amazonas and R. sanchezii as endemic to forests overlooking the Marañon. Additionally, Ecuadoren R. austroecuadorense is recorded for the first time from Peru from forest relics in Huancabamba (Piura) and Chota (Cajamarca). Two new species of Urtica are described, U. urentivelutina as a local endemic on the slopes overlooking the Marañon near Chagual (La Libertad), and U. lalibertadensis which is widespread in La Libertad from Otuzco to Tayabamba. Urtica longispica is reported as new to the flora of Peru and U. macbridei is reported from northern Peru for the first time. Both Urtica and the Ribes andicola group can be considered as indicators of former forest cover, since they tenaciously persist after the felling of the forests. Their distribution indicates that a) some of the current forest fragments were once largely coherent forest belts (e.g., those of Santa Cruz and San Miguel) and b) some areas which have no coherent forest cover at present once had large and coherent montane forests (e.g., large parts of the Prov. Otuzco). Comparing the known distribution data for Urtica, the Ribes andicola group, the Passiflora lobbii group and Nasa (Loasaceae) it becomes evident, that a) the relict forests are still very poorly known, b) they are exceptionally rich in narrowly endemic taxa, some of which are here described and many of which undoubtedly remain to be discovered and c) they represent southernmost outposts for many Ecuadorean species and species groups.